Safety and side effects of suxamethonium in clinical practice – literature overview - Mazur, Bartosz; Greguła, Anna; Stachyrak, Karol; Mika, Dawid; Kłos, Aleksandra; Turek, Kamila; Lambach, Maciej; Pawlicki, Mateusz; Mazurek, Aleksandra; Wilanowska, Wiktoria (Journal of Education, Health and Sport, 2024)
Introduction and purpose Muscle relaxants have been integral to medical practice for decades, benefiting both anesthesiologists for smooth patient intubation and surgeons requiring deep muscle relaxation. This article focuses on succinylcholine, a prominent muscle relaxant, exploring its historical context, efficacy, and the accumulated data on potential life-threatening side effects. The manuscript analyzes the available knowledge regarding the adverse effects of succinylcholine in clinical practice, presenting literature-identified methods aimed at risk mitigation. Summarizing the current understanding of succinylcholine’s risks seeks to enhance its effective use, decrease adverse incidents in patients, and contribute to the overall safety of both patients and healthcare providers. Material and methods The following review of studies was based on articles obtained from the PubMed and Google Scholar databases. Key search terms included suxamethonium, succinylcholine, suxamethonium hyperkalemia, suxamethonium myalgia, suxamethonium anaphylaxis, suxamethonium cholinesterase deficiency, and suxamethonium malignant hyperthermia. Conclusions Suxamethonium’s adverse effects range from muscle pain-related discomfort to rare, potentially lethal multi-organ complications, impacting patients’ health diversely. Despite its drawbacks, succinylcholine remains crucial in anesthesiology. Ongoing research offers avenues to counteract or mitigate side effects. However, these methods necessitate further research to develop universal, widely available protocols in clinical settings.